Riverbed clogging experiments at potential river bank filtration sites along the Ping River, Chiang Mai, Thailand - Pholkern, K.; Srisuk, K.; Grischek, T.; Soares, M.; Schafer, S.; Archwichai, L.; Saraphirom, P.; Pavelic, Paul; Wirojanagud, W. (Springer, 2015)
Riverbank filtration (RBF) is a process during which river water is subjected to subsurface flow prior to abstraction wells, often characterized by improved water quality. The induced infiltration of river water through the riverbed also creates a clogging layer. This decreases riverbed permeability and abstraction rates, particularly if the river water has high turbidity, as in Thailand. As Chiang Mai Province is one of the most favorable sites for future RBF construction in Thailand, two sites, Mae Rim and San Pa Tong, were selected to simulate clogging by using a channel experiment. The mobile experimental apparatus was set up at the bank of the river in order to use fresh river water. Riverbed sediment was used as channel bed and filling material for the columns. The aim was to simulate riverbed clogging using river water with high turbidity and determine the effect of clogging, which can be quantified using vertical hydraulic conductivity (Kv). An increase in channel flow velocity caused partial removal of a clogging layer in only the top 0.03 m of the sediment column. The combination of low channel flow and high turbidity leads to much more clogging than high channel flow and low turbidity. A complete manual removal of the external clogging layer led to an increase in Kv, but the initial Kv values were not recovered. The external clogging had a lower effect on Kv than internal clogging. For planning new RBF sites along high-turbidity rivers, reduction in Kv to estimate RBF well yield cannot be calculated based only on initial Kv but requires field experiments.